Hearing dummies: Individualized computer models of hearing impairment. (October 2014) - Panda, Manasa R.; Lecluyse, Wendy; Tan, Christine M.; Jürgens, Tim; Meddis, Ray
Abstract Objective: Our aim was to explore the usage of individualized computer models to simulate hearing loss based on detailed psychophysical assessment and to offer hypothetical diagnoses of the underlying pathology. Design: Individualized computer models of normal and impaired hearing were constructed and evaluated using the psychophysical data obtained from human listeners. Computer models of impaired hearing were generated to reflect the hypothesized underlying pathology (e.g. dead regions, outer hair cell dysfunction, or reductions in endocochlear potential). These models were evaluated in terms of their ability to replicate the original patient data. Study sample: Auditory profiles were measured for two normal and five hearing-impaired listeners using a battery of three psychophysical tests (absolute thresholds, frequency selectivity, and compression). Results: The individualized computer models were found to match the data. Useful fits to the impaired profiles could be obtained by changing only a single parameter in the model of normal hearing. Sometimes, however, it was necessary to include an additional dead region. Conclusion: The creation of individualized computer models of hearing loss can be used to simulate auditory profiles of impaired listeners and suggest hypotheses concerning the underlying peripheral pathology.